Temperature and ion dual responsive biphenyl-dipeptide supramolecular hydrogels as extracellular matrix mimic-scaffolds for cell culture applications. Issue 20 (27th April 2017) - Bian, Shaoquan; Cai, Hanxu; Cui, Yani; He, Mengmeng; Cao, Wanxu; Chen, Xuening; Sun, Yong; Liang, Jie; Fan, Yujiang; Zhang, Xingdong
Abstract : Illustration of the gelation process of a new aromatic short peptide gelator based on biphenyl and its application in cell culture. Abstract : Stimuli-responsive supramolecular hydrogels composed of aromatic short peptide gelators have attracted intensive attention in the field of biomedicine because of their stable chemical structure, simple and convenient synthetic route and intelligent response to external stimuli. In this paper, several dipeptides were coupled to biphenylacetic acid (BPAA) to generate aromatic short peptide compounds through the standard solid phase peptide synthesis. These BPAA–dipeptide compounds presented clearly different gelation behaviors from the generally employed Fmoc-dipeptide and Nap-dipeptide compounds, but only BPAA-diphenylalanine was able to form homogeneous and transparent hydrogels through temperature switching or ion induction. Utilizing the biphenyl group not only expanded the scope of aromatic molecules serving as building blocks of aromatic short peptide gelators but also demonstrated the critical role of aromatic molecules in the self-assembling process. Moreover, supramolecular hydrogels initiated by heating–cooling or salt addition could be exploited as extracellular matrix (ECM) mimic scaffolds to support the adhesive growth and proliferation of L929 cells in 2D/3D culture under physiological conditions, demonstrating their potential applications in regenerative medicine.